The Niger River Basin : A Vision for Sustainable Management - Andersen, Inger (World Bank, Washington, DC, 2012)
The Niger River Basin Authority (NBA) brings together nine countries to promote integrated water resources management across political borders. The nine - Benin, Burkina Faso, Cameroon, Chad, Cote d'Ivoire, Guinea, Mali, Niger, and Nigeria have embraced a shared vision to build institutional capacity, political agreement, and public support for cooperation. The countries agree that sustainable management and development of the basin's water resources are necessary to meet natural and man-made threats to their shared resources, and that progress can be achieved by integrating technical data on the hydrology and geography of the river system with judicious political and economic policy. The Niger river basin, home to 100 million people, is a vital and complex asset of West and Central Africa. The continent's third-longest river, the Niger is more than just a source of water. For the people of the nine countries it is a source of identity, a route for migration and commerce, a source of conflict, and now a catalyst for cooperation. Niger, with about 23 percent of the Basin within its borders, depends on river navigation (through Nigeria) to reach the sea. Nigeria, a major food grower on rain-fed and irrigated land, is the final downstream country. Its borders enclose some 80 percent of the Basin's population and about 28 percent of its territory.